Literasi Keuangan Digital Sebagai Pemberdayaan Sumber Daya Manusia dalam Mencegah Pinjaman Online Illegal pada Ibu-Ibu Majelis Taklim Al Hasanudin - Pusporini Palupi Jamaludin; Paringsih Paringsih; Elizabeth Tika Kristina H; Budhi Prabowo (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
The importance of implementing community service activities (PKM) in the Tri Dharma of higher education has a positive impact on the community. The title of this PKM is "Empowerment of human resources through digital financial literacy to prevent illegal online lending practices among mothers of Majelis Taklim Al Hasanudin. " The low level of digital financial literacy is the main cause that makes mothers entangled in illegal loans. The purpose of this PKM is to increase the understanding of digital financial literacy, which is crucial for the community to recognise and stay away from unauthorised online loans. With good knowledge, each individual is expected to make smart financial decisions and avoid the trap of illegal debt. This community service activity took place in the Sawah Baru Ciputat area, South Tangerang. The methods used in the implementation of this PKM include participatory approaches, lectures, and focus group discussions (FGDs). The results of this activity show that the participants, namely the mothers of Majelis Taklim Al Hasanudin who have received education, are able to take both preventive and responsive steps to protect themselves from the negative impacts of illegal online loans. Their improved understanding of the characteristics of illegal online loans, the importance of financial planning, and the ability to access legitimate financial information were significant results. Thus, digital financial literacy proved effective in strengthening the capacity of the women to maintain personal financial stability and avoid illegal online lending practices.